THE IMPACT OF COVID-19 ON THE LIVELIHOODS AND SOCIAL WELLBEING OF FEMALE DOMESTIC WORKERS IN DISTRICT ABBOTTABAD, PAKISTAN - Summera Salar; Adeel Jalal Malik; Madiha Tariq (International Journal of Contemporary Issues in Social Sciences, 2024)
The impact of Covid-19 has been particularly harsh, especially for female domestic workers, who face exacerbated challenges in Pakistan. This study delves into the specific effects of the pandemic on their livelihoods. Employing a mixed-method approach, quantitative data was gathered from 60 respondents through interviews, focusing on aspects like livelihoods, working conditions, and changes in household dynamics, while qualitative insights were drawn from in-depth interviews with female domestic workers. The findings reveal stark realities: 45% experienced job loss, and household incomes dropped by 37%. Additionally, 62% reported increased domestic violence, and 68% faced heightened marital stress during the pandemic. Shockingly, 42% went to bed hungry, 58% felt isolated, and a staggering 83% found life to be meaningless. These results underscore the importance of recognizing non-monetary values, such as social wellbeing. It's imperative for national-level policies and state support to target female domestic workers specifically, aiming to enhance their livelihoods and overall quality of life.